Financing SMEs in the Republic Of Croatia - Mirko Pešić (Ekonomski Vjesnik, 2011)
The starting point of every entrepreneurial venture is the entrepreneur him/herself. When initiating a venture of any kind, an entrepreneur faces all the factors that have to be organised and overcome on his/ her own. The main obstacle on this path is the procurement of sufficient funding to go all the way from the original idea to the finished product, or to the enterprise performing a certain activity. The simplest way is when the entrepreneur has initial capital, i.e. sufficient funds to implement the idea into a finished product or enterprise. However, under today’s influence of globalisation, most entrepreneurs do not have this initial capital or sufficient funds to initiate any kind of entrepreneurial venture. This paper provides an insight and explanations of the most common ways in which entrepreneurs can access funds and how they can finance their business venture. Raising funds is one of the greatest challenges for anyone planning to start an entrepreneurial venture.